Application of hull form knowledge graph method in design of Yangtze River bulk cargo ship - Jianyi ZHANG; Lüge XIAO; Baiwei FENG; Zuyuan LIU; Chengsheng ZHAN (Zhongguo Jianchuan Yanjiu)
ObjectiveAiming at the complexity of the navigation environment for shipping on the Yangtze River, as well as the high energy consumption and serious pollution of some ship types, there is an urgent need to carry out research on green and intelligent ship types. In this study, a knowledge graph is applied to the hull form design method so as to adapt to the green and intelligent technological development requirements in the optimization of ship types.MethodsThe knowledge graph and inference model of a Yangtze River bulk cargo ship hull form are introduced, and a knowledge graph-based hull form design process is proposed for the first time to complete the rapid design of an excellent hull form for a 6 000-ton Yangtze River bulk cargo ship. The hull form is then compared with that of a ship designed by conventional methods.ResultsDrag reduction effect of 2.39% is obtained compared with the conventionally designed hull form. ConclusionThe results of this study verify the effectiveness of the proposed knowledge graph-based hull form design method.